MENJAGA KESEHATAN MENTAL REMAJA BERSAMA KOMUNITAS REMAJA MASJID SEJIWA (SEHAT JIWA) - Fitri, Rahma Kusuma (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2025)
Mental health is one of the important aspects in the stages of human development, including adolescents. Adolescent mental health is an increasingly pressing topic because adolescence is a challenging transition period, both physically, emotionally, and socially. During this time, adolescents often face pressure from the family environment, school, peers, and social expectations, all of which can affect their mental well-being. Adolescent mental health will determine how successful adolescents are in completing their developmental tasks and also their quality of life in the future. The existence of appropriate support and attention to adolescent mental health not only helps individuals develop well but also creates a stronger, healthier, and more empowered future generation. This study aims to help build awareness and the role of adolescents as agents of change in adolescent mental health. The results of the study showed that the formation of the Sejiwa mosque adolescent community quantitatively showed a significant difference between the pre-test and post-test scores. The results of the qualitative intervention also showed an understanding of participants regarding adolescent mental health.